Penyuluhan Kesehatan dan Aktivitas Fisik Bersama Anak Jalanan dalam Mewujudkan SDGs dan Pancasila Sila ke-3 - Chalista Cheryl Yonatha; Angelica Crystalina; Sherly Marcellina; Ferdy Anthonius; Christian Siregar (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Health and physical activity counseling is one of the efforts to raise awareness and healthy lifestyle habits, especially for vulnerable groups such as street children. This article is a community service article based on participatory education that aims to increase street children's knowledge about healthy lifestyles and foster simple physical activity habits. This program is also in line with Sustainable Development Goals (SDGs) number 3, namely a healthy and prosperous life. This activity also helps strengthen the values ​​of togetherness and unity as contained in the 3rd principle of Pancasila,